Enhancing a Flipped Statistics First Year Course by Using QT-Clickers. Issue 1 (16th April 2021) - Reyneke, Fransonet; Fletcher, Lizelle; Harding, Ansie
Abstract: This article focuses on the unique contribution of the QT-clicker regarding formative and summative assessment in a large flipped first year statistics module. In this module, the flipped classroom as pedagogical model first substituted the traditional teaching model. QT-clickers were subsequently introduced to enable active and cooperative learning for face-to-face engagement inside the classroom. The various input capabilities of the QT-clicker, providing for the possibility of partial grade crediting, offer a distinguishing advantage. These clickers were initially only used for formative assessment, but soon extended to summative assessment. Two cohorts—2014 (no QT-clickers) and 2017 (with QT-clickers)—were compared. The intervention of using QT-clickers was evaluated along two lines: the pedagogical influence of the QT-clicker and the effect of partial grade crediting. Several general linear models (GLMs) were fitted to the data to investigate how QT-clicker use is related to the students' examination performance. The outcome of the GLM models indicates that the association of higher examination marks with QT-clicker use holds for the 2017 cohort with and without partial credit. A qualitative component of the study reports on the student voice testifying to positive experience.